Soy formulas in the pediatrician’s practice - V. P. Novikova; O. A. Bokovskaya; E. A. Turganova (Лечащий Врач)
Background. Using soy formulas in infant nutrition goes back more than 100 years. They have evolved from simple mixtures based on ground roasted beans to high-tech modern products based on soy protein isolate. Due to their high nutritional value, soy formulas remain a popular alternative when it comes to choosing a dairy-free diet. But there is still an ongoing debate about their safety, with particular attention being paid to the content and activity of phytoestrogens. In 2021, an international consensus of experts recognized soy formulae as safe for growth and development based on available scientific evidence. However, research continues, and with the growing popularity of plant-based diets, soy continues to be a focus of attention for scientists around the world. From the uncontrolled use of soy formulas in the past, the trend has long since shifted to using them as a specialized product for indications under medical supervision. Soy formulae are included in major international recommendations as second-line dietary therapy for cow's milk allergy. Allergy prevention with soy formulae, however, remains open and requires further research. Soy formulae are the product of choice for galactosemia and can also be used for diarrhea. They remain in the pediatrician's practice, but require certain prescribing guidelines.   Objective. This article reviews the recommendations of leading experts and regulators on the use of soy protein isolate-based infant formulas.